The barley grain thioredoxin system – an update - Hägglund, Per; Björnberg, Olof; Navrot, Nicolas; Mørch Jensen, Johanne; Maeda, Kenji; Kirkensgaard, Kristine; Shahpiri, Azar; Sultan, Abida; Bunkenborg, Jakob; Gubler, Frank; Barrero, José M.; Henriksen, Anette; et al. (Frontiers in Plant Science, 2013)
Thioredoxin reduces disulfide bonds and play numerous important functions in plants. In cereal seeds, cytosolic h-type thioredoxin facilitates the release of energy reserves during the germination process and is recycled by NADPH-dependent thioredoxin reductase. This review presents a summary of the research conducted during the last ten years to elucidate the structure and function of the barley seed thioredoxin system at the molecular level combined with proteomic approaches to identify target proteins.